Transkarbams with terminal branching as transdermal permeation enhancers - Klimentová, Jana; Kosák, Petr; Vávrová, Katerina; Holas, Tomás; Novotný, Jakub; Hrabálek, Alexandr (Bioorganic & medicinal chemistry letters, 2008)
Transkarbams (T) represent novel group of highly active, non-toxic transdermal permeation enhancers. This study was focused on the influence of small symmetrical terminal branching on their enhancing activity. Series of T with terminal methyl or ethyl branching was prepared and their permeation-enhancing activity was compared to that of their linear analogues. The results showed completely a different behaviour from similarly branched alcohols, supporting the key role of the ammonium-carbamate polar head in the enhancing activity of T.
Keywords: Animals; aplikace kožní; karbamáty; Skin Absorption; theofylin; zvířata; Administration, Cutaneous; Theophylline; Carbamates; prasata; Skin; Swine; kůže; kožní absorpce; permeabilita; Permeability